Silentious - Freeman, Shannon (Shannon Ford) (Freeman, Shannon (Shannon Ford). Summit Middle School, 2015)
Mai Pham is excited to go back to school after holiday break, especially now that Carson is there. However, now Carson has gone too far, encouraging shy Mai to sing in the school talent show--even after her father forbids her to compete.